Care ethics of women as institutionalization of equality and peace building at grassroots level in West Java - sumadi sumadi (State Institute of Islamic Studies (IAIN) Salatiga, 2018)
This paper is based on the background that peace is a necessity which should always be maintained. Surveys often show West Java as a province with the highest cases and events of discrimination compared with other regions in Indonesia. However, people of West Java have established many peace building movements at central and grassroots levels. Interestingly, peace building movements are often started by women. Peace building can be an area of gender equality. This study was a qualitative study with in-depth interview and observation. The research result showed that women with care ethics who joined peace building were able to contribute as strong social glue in the field. The care ethics of women in their activities also institutionalized equality.